Nutritional and Anti-nutritional Levels of Some Local Vegetables(Vernomia anydalira, Manihot esculenta, Teiferia occidentalis, Talinum triangulare, Amaranthus spinosus) from Delta State, Nigeria - PO Agbaire (Journal of Applied Sciences and Environmental Management)
Levels of nutritional and antinutritional levels of five leafy green vegetables from Delta State, Nigeria were assessed. Analyses were done using standard analytical methods. Crude protein, crude lipid, carbohydrate, moisture, ash, crude fiber and colorific values, had values 4.74%±1.48, 4.78% ± 0.62, 4.98% ± 1.79,80.84% ± 4.69,1.96% ± 0.19,2.00% ± 1.25,78.92 ± 21.94Kcal/100g respectively. The mineral contents were; sodium 4.83 ± 0.29ug/g, calcium 2.18 ± 1.54ug/g, potassium 0.97 ± 0.04ug/g, magnesium 1.61 ± 0.20ug/g, iron 0.34 ± 0.21ug/g, zinc 0.04 ± 0.03ug/g, phosphorus 1.43 ± 0.81ug/g, copper 0.09 ± 0.13ug/g. The antinutrient compositions are oxalate 1.43 ± 0.61mg/l, phytate 9.15 ± 2.31mg/l and hydrocyanide 0.15 ± 0.1mg/l. These results showed that these vegetables contain an appreciable amount of nutrients, mineral elements and low levels of anti-nutrients and should be included in diets to supplement our daily allowance needed by the body. @JASEM